Martianus Capella’s calculation of the size of the moon - Carman, Christian Carlos (2016)
The eighth book of Martianus Capella’s famous De Nuptiis Philologiae et Mercurii deserves a prominent place in the history of astronomy because it is the oldest source that came down to us unambiguously postulating the heliocentrism of the inner planets. Just after the paragraph in which Capella asserts that Mercury and Venus revolve around the Sun, he describes a method for calculating the size of the Moon, as well as the proportion between the size of its orbit and the size of the Earth. It is possible to find some descriptions of the argument in general histories of astronomy or in books dedicated to Capella’s work, but usually they do not try to make sense of the argument. Rather, they limit themselves to describe or paraphrase what Capella says. As far as I know, there is no single study of the argument itself. The explanation for this absence is simple: the calculation offers many difficulties in its interpretation, for it shows obvious inconsistencies in the steps of the argument and apparent arbitrariness in the selection of the data used. In this article, I offer an interpretation that tries to discover, behind Capella’s confusing presentation, a well-sound argument for calculating the Moon’s absolute size. Interestingly, we have no records of this argument in other sources, at least in the form described by Capella.